The Implementation of Discipline as a Promoter of Student Success - Fellix Gosal; Jones Ted Lauda Woy (Universitas Muhammadiyah Enrekang, 2024)
Discipline is an important element in education that can influence students' academic performance. Discipline is defined as the attitude and feeling of obedience and compliance towards values that are considered a responsibility. This study aims to examine the importance of discipline in education and its benefits and implications. The methodology used is qualitative research with a literature review approach, collecting data through journal and book literature to observe social phenomena related to discipline in education. Discipline in education includes appreciation, respect, and compliance with rules, both written and unwritten. Education is a process to improve individuals' abilities, knowledge, and skills through teaching, training, and development. Therefore, education and discipline are two interrelated aspects that play a role in forming quality human resources. In conclusion, discipline in education has an important role in shaping students' character and performance. Consistent implementation of discipline can help create a conducive educational environment and produce individuals who are qualified and ready to face future challenges